Sosialisasi Pembuatan Bahan Ajar Digital Berbasis Pendidikan Karakter Bagi Guru Di Daerah 3T - Jayanti Syahfitri; Muntahanah Muntahanah; Titi Darmi (STMIK Royal, 2023)
Character education is one of the mental revolution efforts made to instill character in students. Teachers play an important role in producing generations of noble character and morality, including elementary school teachers. Instilling character from an early age is expected to be able to strengthen the foundation in building the nation. The process of cultivating character must be adapted to the stages of student development and the times, so that integrating it into interactive teaching materials will be preferred by students, students can more easily understand the material and have skills that are balanced between science and technology and IMTAQ. To realize this, teachers are required to be able to integrate it into PBM such as teaching materials. However, the facts on the ground show that teachers in partner schools do not really understand the context of character building and apply it to teaching materials. The purpose of this activity is to increase teacher knowledge and skills in designing and integrating character education in digital teaching materials. This service activity is carried out through lecture methods, outreach, training, and discussions involving approximately 17 elementary school teachers. The results of the activity show that in general the teacher already knows the concept of character education, examples of assistive applications in making teaching materials and teachers have been able to design and integrate character education into teaching materials in accordance with the subjects being taught which are then ready to be made into digital teaching materials Keywords: socialization; digital teaching materials; character education Abstrak: Pendidikan karakter merupakan salah satu upaya revolusi mental yang dilakukan untuk menanamkan karakter pada siswa. Guru memegang peranan penting dalam menghasilkan generasi yang berkarakter dan berakhlak mulia, tidak terkecuali guru SD. Penanaman karakter sejak usia dini diharapkan mampu memperkuat pondasi dalam membangun bangsa. Proses penanaman karakter harus disesuaikan dengan tahap perkembangan siswa dan perkembangan zaman, sehingga mengintegrasikannya ke dalam bahan ajar interaktif akan lebih disukai siswa, siswa lebih mudah memahami materi dan memiliki keterampilan yang seimbang antara IPTEK dan IMTAQ. Untuk mewujudkan hal ini guru dituntut mampu mengintergasikannya ke dalam PBM seperti bahan ajar. Namun, fakta dilapangan menunjukkan bahwa guru-guru di sekolah mitra belum terlalu memahami konteks pendidikan karakter serta menerapkannya ke dalam bahan ajar. Tujuan kegiatan ini yaitu meningkatkan pengetahuan dan keterampilan guru dalam mendesain serta mengintegrasikan pendidikan karakter dalam bahan ajar digital. Kegiatan pengabdian ini dilakukan melalui metode ceramah, sosialisasi, pelatihan, dan diskusi dengan melibatkan lebih kurang 17 orang guru SD. Adapun hasil kegiatan menunjukkan secara garis besar guru sudah mengetahui konsep pendidikan karakter, contoh aplikasi bantu dalam membuat bahan ajar dan guru telah mampu mendesain serta mengintegrasikan pendidikan karakter ke dalam bahan ajar sesuai dengan mata pelajaran yang diampu yang kemudian siap untuk dibuat ke dalam bahan ajar digital.Kata kunci: sosialisasi; bahan ajar digital; pendidikan karakter